2006
DOI: 10.1038/ncb1522
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein tyrosine phosphatase 1B by sumoylation

Abstract: Protein-tyrosine phosphatase 1B (PTP1B) is an ubiquitously expressed enzyme that negatively regulates growth-factor signalling and cell proliferation by binding to and dephosphorylating key receptor tyrosine kinases, such as the insulin receptor. It is unclear how the activity of PTP1B is regulated. Using a yeast two-hybrid assay, a protein inhibitor of activated STAT1 (PIAS1) was isolated as a PTP1B-interacting protein. Here, we show that PIAS1, which functions as a small ubiquitin-like modifier (SUMO) E3 lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
87
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 27 publications
3
87
0
1
Order By: Relevance
“…Sumoylation can modulate the specific interaction with kinases or phosphatases by changing substrate surfaces and activity. In particular, sumoylation of protein-tyrosine phosphatase 1B has been shown to reduce catalytic activity and therefore change the phosphorylation status of substrates (76).…”
Section: Discussionmentioning
confidence: 99%
“…Sumoylation can modulate the specific interaction with kinases or phosphatases by changing substrate surfaces and activity. In particular, sumoylation of protein-tyrosine phosphatase 1B has been shown to reduce catalytic activity and therefore change the phosphorylation status of substrates (76).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show a previously unexplored aspect of SENP1 function in the regulation of macrophage activation by targeting a phosphatase PTP1B. SUMOylation represses the de-phosphorylation activity of PTP1B and inhibits the negative effect of PTP1B on insulin receptor signaling as well as transformation by the oncogene v-crk (Dadke et al, 2007). This study shows that SUMOylation of PTP1B can reduce its inhibition to STAT3 in IFN-γ signaling.…”
Section: Discussionmentioning
confidence: 83%
“…We observed an accumulation of SUMOylated PTP1B protein in Senp1−/− but not in Senp1+/+ cells ( Figure 3A), indicating that SENP1 functions as a specific de-SUMOylation protease for PTP1B. SUMOylated PTP1B impairs its intrinsic phosphatase activity (Dadke et al, 2007). We treated cells with PTP1B-specific inhibitor, and found that PTP1B inhibition augmented STAT3 phosphorylation but reduced STAT1 activation, which mimicked the response of SENP1-deficient macrophages to IFN-γ signal ( Figure 3B).…”
Section: Senp1 Negatively Regulates Stat3 Activity By Desumoylating Pmentioning
confidence: 93%
See 1 more Smart Citation
“…Elle est en outre impliquée dans la régulation de la signalisation de l'insuline via son activité de phosphatase sur de nombreux récep-teurs à activité tyrosine kinase. La sumoylation de PTP1B en réponse à l'insuline diminue à la fois l'activité et l'expression de PTP1B [13]. Ce mécanisme pourrait participer au contrôle neuronal de la prise alimentaire.…”
Section: Synthèse Revuesunclassified